Relation between adaptive function and IQ among youth with histories of heavy prenatal alcohol exposure. Issue 12 (4th February 2019) - Doyle, Lauren R.; Coles, Claire D.; Kable, Julie A.; May, Philip A.; Sowell, Elizabeth R.; Jones, Kenneth L.; Riley, Edward P.; Mattson, Sarah N.; ,
Abstract: Background: Adaptive function and general intellectual function are two important and often correlated domains. While youth with prenatal alcohol exposure frequently demonstrate impairments in both domains, it is not clear whether the relation between these domains is consistent across levels of ability or whether, for example, adaptive function is less affected by intellectual function at higher ability levels. The aim of the current study was to test this relation in youth with and without prenatal alcohol exposure. Methods: As part of the Collaborative Initiative on Fetal Alcohol Spectrum Disorders, Phase II, subjects with heavy prenatal alcohol exposure (AE) and nonexposed subjects with and without other clinical conditions or concerns (CON) completed a comprehensive neurobehavioral battery. Multiple regression analyses tested the relation between full scale IQ (FSIQ) and overall adaptive function. Interaction terms between Group and each variable were created to formally test for group differences. Three subsequent regression analyses tested which adaptive function domains (Communication, Daily Living Skills, Socialization) significantly contributed to results. Follow‐up analyses examined correlations based on IQ range (low IQ <85; high IQ ≥85). Results: The interaction between FSIQ and Group on overall adaptive function was significant; the relationship between FSIQ and adaptive function was weaker in the AE group than in the CON group. Regarding specific adaptive function domains, the interaction between FSIQ and Group was significant only in the Communication domain. Follow‐up analyses showed, within the low IQ range, the correlation between FSIQ and Communication was stronger in the CON group than the AE group. Within the high IQ range, the correlation between FSIQ and Communication was significant only in the CON group. Conclusions: Although higher intellectual functioning was associated with better adaptive function ability among controls, this was not found among the alcohol‐exposed youth where a general dampening of adaptive ability was noted. Further, the differential relationship between IQ and adaptive function between groups appears to be driven by communication abilities. These findings suggest that level of intellectual functioning of children with prenatal alcohol exposure does not fully account for caregiver‐reported communication and overall adaptive function deficits particularly at higher levels of functioning.